(untitled) (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2022)
Lake Chad in the Sahel region has emerged as the epicenter of the widening conflict that is, in part, attributed to climate change-induced factors along with natural resource instability and intra-state pressures exacerbated by exploitative past colonial policies. The resulting environment-conflict nexus has given rise to violence, state fragility, communal breakdown, displacement of the local population, the proliferation of violent non-state actors, and a vicious cycle of poverty in countries surrounding Lake Chad. These factors, in turn, have made the individuation, establishing, and sustaining of institutions, and aid mechanisms to alleviate climate-change-related hardships extremely difficult. Furthermore, the environment-conflict nexus has disrupted inter- and intra-state migration patterns in Lake Chad, thereby adversely affecting agricultural yields and water resources. Additionally, there is a limited political representation and inadequate access to governmental services in the worst affected regions, which negatively accrue several contributing factors of the environment-conflict nexus.